Substitution of Soybean Meal with Distiller’s Dried Grains with Solubles and Its Effect on Physical Parameters of Broiler Diets - Kumar, Sushil; Sihag, Zile Singh; Sihag, Sajjan; Singh, Narender (Indian Journal of Animal Nutrition, 2017)
Effect of replacement of soybean meal (SBM) with distillers dried grains with solubles (DDGS) along with supplementation of the lysine on the physical parameters of the broiler diets was determined. DDGS was added at 15, 30 and 45% along with lysine at the level of 0, 0.50, 0.75 and 1% to each DDGS based diet. The bulk density of diets with 45% replacement of SBM with DDGS was higher (P<0.05) than other diets. Reduction in the particle size and an increase in surface area and number of particles/g in the starter as well as finisher diets was significant (P<0.05) with increased DDGS level. At same DDGS level, the values of particle size, surface areaand number of particles/g of the diets were similar with increased lysine level. The relative proportion of coarse and medium sized particles decreased while that of fine particles increased linearly (P<0.05) with increased DDGS and lysine levels both in starter and finisher rations. A decrease (P<0.05) in modulus of fineness was observed with increasing DDGS level while increasing lysine level did not affect modulus of fineness.